The power of EFL student-researchers: A critical discourse analysis project “Hey, teachers, leave them kids alone” - Nihal Sadek; Rena Sassi (Studies in English Language and Education, 2017)
Learner autonomy has been called for by many researchers in language teaching. Learner independence can be achieved through empowering students (Ss) by training them on ways to learn certain learning strategies rather than just teaching them certain linguistic features. This goal can be attained through implementing the learner-as-researcher approach called for by many researchers due to its potential ability to involve Ss in their learning process. This paper presents the findings of a multifaceted action research project intended to enhance Ss’ critical skills through implementing the Riggenbach Model (1999) to a linguistic micro aspect; learn more about Teacher –Student (T-S) interactions through critically analyzing a number of T-S interactions using Dobbs’ analysis model presented in Celce-Murcia and Olstein (2000), and use critical classroom discourse analysis (CCDA) to provide a macro-analytic explanation of identity and power relations of the Ss by examining student reflections and final products.